Fostering Competence for Sustainability through Education and Adaptive Global Citizenship - Mardikaningsih, Rahayu; Masnawati, Eli; Aisyah, Nur (Journal of Social Science Studies, 2021)
This paper explores how education systems can nurture twenty-first-century skillsets that contribute meaningfully to global sustainability. By examining interdisciplinary literature, it identifies the competencies essential for addressing environmental, social, and economic challenges in the twenty-first century, including critical thinking, collaboration, digital literacy, emotional intelligence, and ethical leadership. The study emphasizes the need for transformative pedagogies, experiential learning, and systems thinking to empower students as proactive change agents. It argues that education should not only transmit knowledge but also cultivate agency, responsibility, and adaptability. The integration of global and intercultural competencies enhances learners’ ability to navigate pluralistic societies and transboundary dilemmas. Institutional strategies such as whole-school approaches, community partnerships, and performance-based assessments are highlighted as key enablers of sustainability education. Furthermore, teacher training is identified as a pivotal factor in ensuring that these skills are effectively imparted. The discussion concludes by asserting that the alignment of education with sustainability is not optional but essential for future resilience. Through intentional design and inclusive implementation, education can become a transformative force in realizing just and regenerative societies.